Leaf photosynthesis: do endophytes have a say?. (October 2022) - Suryanarayanan, T.S.; Ayesha, M.S.; Shaanker, R. Uma
Abstract : Endophytes, both bacterial and fungal, constitute an integral component of the leaf ecosystem. Here we argue that the respiratory metabolism of endophytes in the intercellular spaces of leaves could have a significant role in enhancing leaf photosynthesis by enriching the internal CO2 concentration, especially in C3 plants.